Interrogating the Perceptions of Undergraduate Pharmacology Teaching on an MBBS Programme at a UK Medical School - Eleanor Renee Smith; Maximilian Paley; Raji Kaur Lalli; Maryam Malekigorji; John Broad (Pharmacology Research & Perspectives)
ABSTRACT Pharmacology education at medical schools in the UK aims to give newly qualified doctors the ability to apply foundational knowledge of pharmacology and to be able to prescribe drugs safely. This study aimed to assess a current pharmacology curriculum and understand the perspectives of both students and educators around pharmacology teaching. Employing a mixed‐methods approach, the research utilized documentation analysis, focus groups, semi‐structured interviews, and online questionnaires with students, educators and senior academic tutors. The analysis of the current curriculum revealed that 1069 drugs or drug classes were introduced to students in their first 2 years of study of drugs and drug classes. Students reported feeling overwhelmed with the number of drugs they were expected to learn. They suggested increasing contextual learning experiences and more practical prescribing experience. Students emphasized the need for greater visibility of pharmacology teaching. Students and educators identified challenges in integrating pharmacology effectively, which contributed to knowledge gaps. Disparities between students' perceptions of pharmacology education and educators' confidence in its delivery were found. These findings suggest the need to address the number of drugs introduced to students in their first 2 years of study. Recommendations include reducing the number of drugs or drug classes introduced to students, highlighting important drugs or classes, enhancing the visibility of pharmacology in the curriculum, and educating and supporting staff when preparing teaching sessions that involve pharmacology. These measures may address students' feelings of being overwhelmed by pharmacology, aligning with the aim of developing medical students into safe prescribers following graduation.